Understanding the mechanisms through which women's group community participatory intervention improved maternal health outcomes in rural Malawi: was the use of contraceptives the pathway? - Collins O. F. Zamawe; Chrispin Mandiwa (Taylor & Francis Group, 2016)
Background: Women's group intervention is a community based initiative through which rural women form groups, meet regularly to discuss maternal health issues affecting them, and come up with locally available solutions. This intervention has been associated with reduced maternal and neonatal mortality in limited resource settings. Nevertheless, the mechanisms through which women's groups influence maternal health outcomes are uncertain. Because contraception reduces the risk of maternal mortality and women's groups also tackled this issue, we speculated that contraceptive use might be the pathway. Consequently, this study investigated whether participation in women's groups was associated with contraceptive use in Malawi. Design: We examined the use of contraceptives between women who participated in women's groups and those who did not through a community-based cross-sectional study in Mchinji, Malawi. The study involved 3,435 women of reproductive age (15-49 years) who were recruited using a multistage sampling approach. Members (treated) and non-members (control) of women's groups were matched on observed covariates using propensity scores and the counterfactual for the treated individuals was estimated. Results: Crude analysis revealed that women's groups improved uptake of contraceptives by 26% (odds ratio (OR)=1.26; 95% confidence interval (CI)=1.03-1.56; p=0.024). However, using the matched data, uptake of contraceptives was almost the same among members and non-members of women's groups. More precisely, the likelihood of using contraceptives was not significantly different between the members and non-members of women's groups (OR=1.00; 95% CI=0.81-1.24; p=0.991). Conclusions: There is insufficient evidence of an association between participation in women's groups and contraceptive use among rural Malawian women. The implication is that contraception was not the mechanism through which women's groups contributed to reduced maternal mortality in Malawi. Because the effects of community interventions are usually comprehensive and sometimes difficult to demonstrate, ethnographic studies should be considered in the evaluation of women's groups and other related interventions.